Effects of Commercial Laccase Enzyme on Appearance and Light Fastness of Lingocellulosic Jute Yarn - Zolriasatein, A.A.; Yazdanshenas, M.E.; Khajavi, R.; Rashidi, A.S. (Asian Journal of Chemistry, 2011)
In this paper, a commercial laccase enzyme Denilite II S was applied on jute yarn. In comparison to control yarn, the enzyme treated sample shows declined in whiteness, yellowness, brightness index and reflectance characteristics. Because of poor light fastness of this type of fiber due to phenolic lignin component, the effect of laccase enzyme on properties of jute yarn was examined. Enzyme treated yarn shows higher light fastness while lower yarn count and tenacity, because the amount of lignin decreased. The FTIR spectroscopy of bio-treated yarn exhibited oxidation of -CH3 and -CH2- groups into consideration and the amount of carboxylic or ester groups were less than control yarn.